A rare case of disseminated sarcoidosis presenting with neurosarcoidosis: a case report - Abdul Sukur, Noorhafini; Sulaiman Sahari, Narisa; Marwan, Abdul Aziz; Ismail, Rosmadi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Sarcoidosis is characterized by formation of inflammatory granulomas affecting all over the body, with pulmonary predilection (1). Neurosarcoidosis is a rare but potentially dangerous manifestation of sarcoidosis. We report a case of disseminated sarcoidosis presenting with a neurological diagnostic dilemma. Worsening mediastinal lymphadenopathy, together formation of lung and liver nodules making a sarcoidosis diagnosis favourable. Histology from these lesions showed non-caseating granulomatous inflammation. She was treated as a rare case of disseminated sarcoidosis. To date, there is no specific or clear guideline on the management of disseminated sarcoidosis.